Child-Friendly Classroom Management in Islamic Elementary School During the Covid-19 Pandemic - Pamuji, Zuri; Sholeh, Muhammad (Universitas Pendidikan Ganesha, 2022)
The COVID-19 pandemic has had a significant impact on primary education. This opens up the potential for problems in classroom management that are less child-friendly, neglecting children's potential, not being conducive to the learning atmosphere, and even giving rise to non-violence in learning. So it is necessary to look for a child-friendly classroom management model during the Covid-19 pandemic that the teacher carries out. This study aims to analyses in depth the role of teachers in managing the class toward being child-friendly. This study used the descriptive qualitative method with a single case study design. Collecting data using interview techniques with six teachers who teach lower grades, learning observations, and documentation. The data analysis uses data reduction, data display, and conclusion. The results show the pattern used by the teacher includes planning, implementation, and reflection. Planning is carried out by focusing on developing student potential, including compiling indicators of competency achievement and learning media (online/offline), so as to minimize the potential for acts of violence and discrimination. For the learning process, the teacher uses sentences or greeting words that are polite and respects students, uses proactive strategies in learning, and handles disciplinary behavior in students without discrimination and violence.